Antibiogram and Phytochemical Analysis of Cinnamon, Clove, and Sichuan Pepper Extracts - Adhikari, Bibek; Shah, Pradeep Kumar; Karki, Roman (Nepal Journal of Biotechnology, 2021)
A wide range of medicinal plant extracts has phytochemicals that possess antimicrobial properties and these plants are used to treat several infections. The study aimed to assess the antimicrobial activities of some spices extracts and to evaluate the phytochemicals present in them. The extracts of spices were prepared using Soxhlet apparatus refluxing with methanol and ethanol. The well diffusion technique was implemented for the evaluation of antimicrobial activities of the extracts and the zone of inhibitions was recorded in millimeters. The antimicrobial test was done against five bacterial isolates: Escherichia coli, Proteus mirabilis, Pseudomonas aeruginosa, Salmonella enterica serotype Typhi, and Staphylococcus aureus and a fungal isolate: Candida albicans. The extracts were concentrated by Rotary Vacuum Evaporator and a stock solution of 200 mg/mL was prepared by dissolving in 10 % DMSO. Concentrations of 40, 60, 80 and 100 mg/mL extracts were used for antimicrobial activity. The result of this study showed that clove extracts had the highest antimicrobial property against all the test microorganisms. Methanolic extract of clove had the highest inhibitory effect against Proteus mirabilis (24.21±0.15 mm), Pseudomonas aeruginosa (19.78±0.23 mm), and Candida albicans (20.07±0.08 mm) whereas ethanolic extract was effective against Escherichia coli (20.44±0.16 mm), Salmonella Typhi (21.66±0.31 mm) and Candida albicans (21.11±0.09 mm). Cinnamon and pepper extracts, leaving some exceptions, also had antimicrobial properties. The presence of phytochemicals: polyphenols, flavonoids, and tannins are the major components responsible for antimicrobial activity. Thereby, this study successfully demonstrated the possibilities of using spices extracts in the treatment of microbial infections.